Norman O. Brown, Herbert Marcuse and the romantic tradition - Greenham, David (2001)
This thesis presents the work of Norman O. Brown and Herbert Marcuse as responses to romantic problematic obtained first and foremost from the legacy of Immanuel Kant’s critical philosophy, and, secondly, from the first significant American realisation of this inheritance in the writings of Ralph Waldo Emerson. The importance of this romantic reading is that it escapes the usual interpretations of Marcuse and Brown in terms of Marxism and Psychoanalysis, instead tracing the significance of their thought to an earlier philosophical foundation in Europe and America. Kant and Emerson remain touchstones throughout; and it is through them that, in Chapter 1, I have determined what I shall be calling romanticism in an American context, reading Emerson’s essay ‘Experience’ (1844) as an exemplary occasion. In Chapter 2, two of the major works of Marcuse and Brown, Eros and Civilization (1956) and Life Against Death (1959) are examined philosophically in terms of their dialectical rethinking of narcissism, showing how they begin to respond to the romantic question set out in Chapter 1. In Chapter 3, I ex-amine the use of myth and aesthetics, paying particular attention to the integrity of the failings of Marcuse’s aesthetic theory, which stem from its romantic origins in Kant and Schiller. Chapter 4 is a reading of Brown’s Love’s Body (1966), presented against Marcuse’s criticisms (1967), in which I establish the importance of symbolism and originality for Brown, tracing them again to themes present in Kant and Emerson. Chapter 5 interprets Brown’s Closing Time (1973) through an extensive reading of that book’s primary source, the proto-romantic Giambattista Vico’s New Science (1744). The Conclusion locates Brown and Marcuse within the myth and symbol tradition of American Studies, showing how they re-vision America as a romantic ideal.